PERAN VALUE CHAIN PADA PEDAGANG GROSIR DALAM HUBUNGANNYA STRATEGY PEMASARAN - Ismail, Anas (Benefit, 2013)
In the wholesale business is closely related to customer satisfaction. Lots of different ways to make customers feel satisfied and it is important to keep them coming back wholesale to grocery stores them. At this level of business turnover is very fast and requires significant attention to keeping the existing inventory. Therefore, the determination of the right supplier is crucial closely related to the existing value chain in the store. There are several important components of concern in this study. These components are in the form of service, price, delivery order and availability of goods. Based on these survey results can be known percentage of the price plays animportant role on the level of sales of grocery stores. While little change will greatly affect the priceof the sale of goods. While the lowest is the delivery order will does not mean that these componentsshould be excluded from the wholesale business to attract customers.